Traditional Engklek Game for Counting Skills of Children Aged 5-6 Years in Jambu Village Kayan Hilir District - Siska Sumarni; Halida; Lukmanulhakim; Horeb Rohait (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Purpose – This study was conducted to explore the role of the traditional game engklek in developing numeracy skills among children aged 5–6 years. The topic is relevant as early childhood education should align with children's developmental characteristics, particularly learning through play. The research argues that traditional games, beyond entertainment, have significant educational value when integrated into early learning practices.Design/methods/approach – This research employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with children and adult informants, and documentation of play activities. Thematic and descriptive analysis was conducted, supported by triangulation to ensure data validityFindings – The results revealed that the engklek game effectively stimulates children's numeracy skills, especially in recognizing numerical sequences, understanding quantity concepts, and identifying number symbols through enjoyable, tangible experiences. The game supports active learning embedded within the children’s sociocultural contextResearch implications/limitations – The study was limited by a narrow participant scope and focused on a single form of traditional game, thus not encompassing the diversity of local play practices. Nevertheless, the findings suggest the importance of revitalizing traditional games as part of a contextual and holistic approach to early childhood education.